Alkali-activated bricks made with mining waste iron ore tailings. (June 2022) - H.K., Thejas; Hossiney, Nabil
Abstract: In India, the enormous growth in the housing sector has put tremendous pressure on construction materials such as bricks. Conventional brick production methods include fired bricks and cement blocks. However, conventional methods significantly contribute to environmental carbon emissions and therefore alternative brick production methods have caught the attention of several researchers. Furthermore, the waste generated in various industries can be a useful resource for the construction industry, and in particular, voluminous waste is generated during the beneficiation stage of iron ore concentrate, which can be integrated into the construction industry to achieve sustainable practice. With this quest in mind, this study proposes the utilization of mining waste iron ore tailing (IOT) in alkali-activated bricks. For this purpose, six different brick compositions were synthesized with fly ash, GGBS, and IOT along with Na2 SiO3 sol. The raw materials were characterized using various techniques such as X-ray fluorescence (XRF), X-ray diffraction (XRD), scanning electron microscope (SEM), and particle size analysis (PSA). Furthermore, a series of standard tests were conducted on the developed bricks to evaluate their strength and durability properties. The developed bricks have presented a maximum compressive strength of 18.45 MPa and minimum water absorption of 12.6%. Besides, the alkali-activated bricks have shown excellent resistance to brick ageing which was attributed to improvement in the microstructure of bricks due to the filling up of voids with products of the polymeric reaction. Finally, it was interesting to notice that with 8% Na2 SiO3 as an alkaline activator and with the combination of fly ash and GGBS more than 50% IOT can be utilized to produce good quality bricks at ambient curing conditions.